Detox Fashion Sustainable Chemistry and Wet Processing - Muthu, Subramanian Senthilkannan; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This second volume on detox fashion covers five key aspects relevant to the topic sustainable chemistry and wet processes: Sustainable Chemicals: A Model for Practical Substitution; Sustainable Wet Processing; Coloration and Functional Finishing of Cotton with Plant Extracts; Call for an Environmental Impact Assessment of Bio-based Dyeing-an Overview; and Enzymes: Biocatalysts for Cleaning Up the Textile and Apparel Sector. The book also presents interesting solutions at the level of the supply chain with regard to sustainable chemistry and wet processes.
1. Sustainable chemicals: A model for practical substitution -- 2.Sustainable Wet Processing- An Alternative Source for Detoxifying Supply Chain in Textiles -- 3.Green Dyeing of Cotton- New Strategies to Replace Toxic Metallic Salts -- 4.Call for environmental impact assessment of bio-based dyeing - an overview -- 5.Enzyme: A bio catalyst for cleaning up textile and apparel sector.
Keywords: Manufactures; Industrial engineering; Production engineering; Environmental chemistry; Business logistics; Green chemistry; Chemistry, Technical; Machines, Tools, Processes; Industrial and Production Engineering; Environmental Chemistry; Supply Chain Management; Green Chemistry; Industrial Chemistry